Self-Help in Mental Health A Critical Review - Harwood, T. Mark.; L'Abate, Luciano; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
They$1 (Bre fast, cheap, and promise amazing results$1 (Bno wonder more people seek mental health advice from self-help books and sites rather than seeking therapy. Complicating this picture: many resources are inappropriate, ineffective, even dangerous. For the clinicians who would gladly recommend self-help for their clients, the challenge is finding reliable, evidence-based sources of help among the vast quantities available. Self-Help in Mental Health: A Critical Review guides readers through this plethora of materials, organizing it into useful order, evaluating popular approaches and trends, and recommending clinically valid, science-based resources for specific clinical and sub-clinical problems. Its authors explain how and why such methods work, offering innovative uses for self-help in prevention and promotion, therapy and rehabilitation, including strengthening therapeutic gains (akin to homework in cognitive-behavioral therapy) and encouraging self-reliance. While some may be tempted to write-off all self-help as quackery or therapy-lite, Harwood and L'Abate recognize the potential the self-help movement holds for countering the stigma associated with mental health treatments. Further, self-help resources represent a viable means of reaching under-served populations, and, for some individuals, they are preferable to conventional therapy. Included in the coverage: Recommendations for books, web sites, organizations, support groups, hotlines, and audio-visual materials Depression, anxiety, eating disorders, addictions, and other conditions. Guidelines for evaluating self-help and guided self-support materials. Strategies for integrating self-help with traditional modes of therapy. Assessment tools for determining client appropriateness for self-help. New directions in theories of self-help and self-change. Contraindications for self-help approaches. Concise and comprehensive, Self-Help in Mental Health is timely reading that will enhance the work of psychotherapists and family and couples therapists, as well as researchers in clinical psychology, psychiatry, and other mental health fields.s
to the Field of Self-help in Mental Health -- What Constitutes Self-Help in Mental Health and What Can Be Done to Improve It? -- The Self-Help Movement in Mental Health: From Passivity to Interactivity -- Self-Support Methods: Initiated, Administered, Guided, Maintained, and Monitored by Professionals -- Distance Writing: Helping without Seeing Participants -- Bibliotherapy -- Online Support Groups and Therapy -- Manuals for Practitioners -- Self-help and Self-change Approaches for Specific Conditions Initiated, Administered, Guided, Maintained, and Monitored by Professionals -- Anxiety Disorders -- Mood Disorders -- Eating Disorders: Anorexia, Bulimia, and Obesity -- Addictive Behaviors -- Personality Disorders -- Severe Psychopathology -- Medical Conditions -- Conclusions and Prospects -- Who Benefits by Self-Help and Why?.
Keywords: Philosophy (General).; Psychotherapy; Social work; Psychology, clinical; Psychology; Clinical Psychology; Psychotherapy; Social Work